Discovery and properties of ultra-high redshift galaxies (9 < z < 12) in the JWST ERO SMACS 0723 Field. Issue 3 (21st November 2022) - Adams, N J; Conselice, C J; Ferreira, L; Austin, D; Trussler, J A A; Juodžbalis, I; Wilkins, S M; Caruana, J; Dayal, P; Verma, A; Vijayan, A P
ABSTRACT: We present a reduction and analysis of the James Webb Space Telescope ( JWST ) SMACS 0723 field using new post-launch calibrations to conduct a search for ultra-high-redshift galaxies ( z > 9) present within the Epoch of Reionization. We conduct this search by modelling photometric redshifts in several ways for all sources and by applying conservative magnitude cuts ( m F200W < 28) to identify strong Lyman breaks greater than 1 mag. We find four z > 9 candidate galaxies which have not previously been identified, with one object at z = 11.5, and another which is possibly a close pair of galaxies. We measure redshifts for candidate galaxies from other studies and find the recovery rate to be only 23 per cent, with many being assigned lower redshift, dusty solutions in our work. Most of our z > 9 sample show evidence for Balmer-breaks, or extreme emission lines from H β and [O iii ], demonstrating that the stellar populations could be advanced in age or very young depending on the cause of the F444W excess. We discuss the resolved structures of these early galaxies and find that the Sérsic indices reveal a mixture of light concentration levels, but that the sizes of all our systems are exceptionally small (<0.5 kpc). These systems have stellar masses M* ∼ 10 9.0 M⊙, with our z ∼ 11.5 candidate a dwarf galaxy with a stellar mass M* ∼ 10 7.8 –10 8.2 M⊙ . These candidate ultra high-redshift galaxies are excellent targets for future NIRSpec observations aimed to better understand their physical nature.